2012
DOI: 10.1038/jhg.2012.94
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin pharmacogenetics: development of a dosing algorithm for Omani patients

Abstract: The objective of our present study was to develop a warfarin dosing algorithm for the Omani patients, as performances of warfarin dosing algorithms vary across populations with impact on the daily maintenance dose. We studied the functional polymorphisms of CYP2C9, CYP4F2 and VKORC1 genes to evaluate their impact on the warfarin maintenance dose in an admixed Omani patient cohort with Caucasian, African and Asian ancestries. We observed a 64-fold inter-patient variability for warfarin to achieve stable interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…These include variants in the following genes: CYP4F2 , EPHX1 , GGCX1 , MDR1 , factor VII , APOE , CALU and PZ . The MAF for the CYP4F2 (rs2108622) was 40% among Turkish [42], 30% in Omani [40] and 42% in Egyptians [12]. The EPHX1 encodes for a putative subunit of the vitamin K epoxide reductase complex called: microsomal epoxide hydrolase 1 [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include variants in the following genes: CYP4F2 , EPHX1 , GGCX1 , MDR1 , factor VII , APOE , CALU and PZ . The MAF for the CYP4F2 (rs2108622) was 40% among Turkish [42], 30% in Omani [40] and 42% in Egyptians [12]. The EPHX1 encodes for a putative subunit of the vitamin K epoxide reductase complex called: microsomal epoxide hydrolase 1 [10].…”
Section: Resultsmentioning
confidence: 99%
“…This variant alone was able to explain 45% of the dose variability in Omani [40]. The VKORC1 Asp36Tyr was significantly associated with higher warfarin doses in Egyptians and when added to Shahin et al dosing model it further explained the variability by only 2% [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also demonstrated the influence of age on the dosage of acenocoumarol, but the mechanism of this association has not been fully elucidated yet. [8,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…There are many pharmacogenetic algorithms, previously developed for warfarin in different population groups Huang et al 2009;Mazzaccara et al 2013;Miao et al 2007;Pathare et al 2012;Tham et al 2006;Wei et al 2012), but these for acenocoumarol are considerably less and insufficient (Borobia et al 2012;Cerezo-Manchado et al 2013;Krishna Kumar et al 2013;Markatos et al Table 4 The results from genotyping of selected polymorphic variants in both Bulgarian patients . We used univariate and multivariate linear regression analyses to evaluate major genetic and non-genetic factors and their influence on maintenance of daily dose acenocoumarol in studied cohort of patients.…”
Section: Casementioning
confidence: 97%